Applications of Genomics to Plantation Forestry with Kelampayan in Sarawak - Wei-Seng, Ho; Julaihi, Abdullah; Shing, Yiing Tiong (2012)
Wood-based industries in Sarawak are increasingly encouraged to adapt to " new wood " from planted forests composed of fast-growing species such as Kelampayan with short rotation cycle (6-8 years). The rationale is that natural forests at the most produce about 3m 3 /ha/yr of commercial timber, whereas plantations can produce annually from 10m 3 /ha to 30m 3 /ha of commercial timber. It is estimated at least 30 million seedlings are required for annual planting or reforestation programmes to meet the increasing global demand for raw materials. To date, several molecular genetics studies have been completed for Kelampayan. These include genetic diversity of Kelampayan, genetic marker (SSRs) development, 'Touch-incubate-PCR' approach for preparing plant tissues for high throughput genotyping, and transcriptomics and bioinformatics on wood formation of Kelampayan. This information provides a useful resource for genomic selection of Kelampayan aiming at the production of high value forests for maximum returns.